724. Neurologic Complications in Hospitalized Pediatric Patients with Influenza Infection, A Multicenter Retrospective Study in Korea. (26th November 2018) - Choi, Gwang-Jun; Park, Ji Young; Choi, Joon-Sik; Kim, Bitna; Choi, Sae Rom; Kim, Dong Sub; Kang, Ji-Man; Lee, Jun Wha; Woo, Young-Jong; Lee, Jeehun; Kim, Yae-Jean
Abstract: Background: The aim of the study was to evaluate the incidence and characteristics of influenza associated neurologic complications (IANCs) in hospitalized pediatric patients in Korea. Methods: We performed retrospective review of hospitalized cases of confirmed influenza infection from October 2010 to April 2017. Patient's data were collected from three referral hospitals in different regions of the country. Results: A total 2, 002 laboratory confirmed influenza cases were identified. The median age was 3.3 years old (range 0.0–18.9 years) and 1, 003 patients were male (54%). Influenza A was diagnosed in 1, 357 cases (68%), influenza B in 624 (31%) and both influenza A and B in 21 (1%). Other combined respiratory virus infection was detected in 104 (5.2%) cases. Out of 2, 002 cases, IANCs were identified in 167 cases (8.3%); influenza virus A was detected in 116 (69.4%), B in 50 (29.9%) and both A and B in one case (0.6%). Of 167 cases with IANCs, 25 patients (15%) had underlying neurologic diseases. Eleven patients (11/167, 6.5%) had combined respiratory viral infection (Rhinovirus = 5; respiratory syncytial virus = 3; coronavirus = 2; and bocavirus = 1). The most common diagnosis was a simple febrile seizure (112/167, 67.1%), followed by other seizures (26/167, 15.6%), encephalopathy/encephalitis (17/167, 10.2%), meningitis (7/167, 4.2%), meningism (4/167, 2.4%) and acute ataxia (1/167, 0.6%). In two patients with encephalitis/meningitis, one patient had influenza A and the other patient had influenza B detected by PCR in cerebrospinal fluid. Most of the patients were fully recovered (162/167, 97%) and no neurologic complication occurred in patients who had only initial manifestation of simple febrile seizure. Ten patients (10/167, 6.0%) required hospitalization in intensive care unit. Three patients (3/167, 1.8%) died of encephalopathy ( n = 1) and combined encephalopathy/myocarditis ( n = 2). Pre-existing neurologic disease was a risk factor of IANCs with an odds ratio of 3.94 (95% confidence interval 2.37 to 6.56, P < 0.0001). Conclusion: IANCs is not rare and may cause serious outcome including death. Clinicians should be aware of the increased risk for IANCs in certain patients with neurologic diseases. Disclosures: All authors: No reported disclosures.